Implementasi Program Magang Mahasiswa Program Studi PGSD FKIP UMS Sebagai Penguat Kompetensi Calon Guru SD Tahun 2016/2017 - Prabowo, David; , Dr. Achmad Fathoni, M.Pd (2017)
This study aimed to describe: 1) Preparation of apprenticeship. 2) Implementation of an internship. 3) Evaluation of internship at UMS FKIP PGSD Studies Program. 4) Reveal how apprenticeship programs can strengthen the competence of elementary teacher candidates. The research is a qualitative research, with descriptive, and uses phenomenological approach. Methods of data collection using interviews, observation and documentation. The informants are students of UMS PGSD force in 2013, DPM (supervisor intern) and the teacher tutor. Methods of data analysis using interactive analysis by way of reducing the data-presentation of data and verification data. The results of this study were: 1) Preparation of apprenticeship in study program PGSD FKIP UMS already performing well, the students have done the registration procedure in accordance with the provisions, DPM (supervisor intern) also gave a briefing to the students before they are deployed to the partner schools so that students understand and grasp the purpose of the internship program. 2) The internship program students of UMS PGSD FKIP force in 2013 has been in accordance with the guidelines on internships guidebook. 3) SD partner and DPM provides joint evaluation at the end of the program 4) Implementation of the internship program students of PGSD FKIP UMS can be as reinforcing the competence of prospective elementary teachers because, seen from SKGP (teacher competency standards beginner) turns the competence of beginning teachers are also owned and there the students participating in an internship program as prospective teachers when implementing an internship program in SD partner.